The DEVELOPMENT OF A 360-DEGREE PANORAMA VIRTUAL TOUR AT THE TRI YUDA SAKTI MONUMENT IN BULELENG, BALI - Elvis Rai Putra; I Nengah Eka Mertayasa; I Gede Partha Sindu (Universitas Pendidikan Ganesha, 2026)
Abstract—This study aims to develop a 360-degree panoramic virtual tour of the Tri Yuda Sakti Monument in Buleleng, Bali. This medium is expected to facilitate local government agencies in introducing the monument to the public. The study is also intended to provide the community with an impression of the monument without requiring them to visit the site directly. The research method employed is Research and Development (R&D), with the media development model based on the Multimedia Development Life Cycle (MDLC). The MDLC model consists of six stages: concept, design, material collecting, assembly, testing, and distribution. This study produced a 360-degree panoramic virtual tour of the Tri Yuda Sakti Monument (Tugu Tiga), developed and implemented in accordance with scientific principles.